Fish diversity and associated physicochemical conditions in seaweed farming areas in Bone Gulf Waters, South Sulawesi, Indonesia - FIJWAL PATANGNGARI; MUSBIR MUSBIR; NAJAMUDDIN NAJAMUDDIN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Patangngari F, Musbir M, Najamuddin. 2025. Fish diversity and associated physicochemical conditions in seaweed farming areas in Bone Gulf Waters, South Sulawesi, Indonesia. Biodiversitas 26: 153-165. The waters of Bone Gulf, located on the coast of Bone District, possess a longstanding legacy of fishing gear, specifically small fishing gear with a mesh size of 15 mm, which is in use today because of the substantial population along the coast. Seaweed farming regions have increasingly become alternatives to fishing zones. This research examines fish diversity and environmental factors in seaweed cultivation zones. Fish were obtained from fishermen utilizing fishing gear in seaweed regions, specifically around the Cape (ST 1), the middle (ST 2), and a distant estuary (ST 3) in Bone waters, from February to August 2024. 2375 fish specimens were gathered, encompassing 67 species from 40 families. Increased diversity was noted in species count (15-46), the species diversity index (2.48-3.18), the evenness index (0.832-0.910), the species richness index (2.64-6.96), and the species dominance index (0.057-0.096). The five most frequently captured species were Chanos chanos, Leiognathus fasciatus, Siganus guttatus, Terapon jarbua, Crenimugil seheli, and Lates calcarifer, together with Oreochromis mossambicus, classified as Vulnerable (VU), and Himantura uarnak, classified as Endangered (EN). Principal Component Analysis (PCA) shows that current velocity and depth are the main factors significantly associated with fish stocks. Furthermore, the phosphate, turbidity, nitrate, salinity, temperature, pH, and dissolved oxygen metrics exhibited no significant impact across the three sites. Future research should focus on long-term monitoring of fish population dynamics, investigating the effects of seaweed farming on fish community structure, and formulating sustainable management practices that engage local communities to preserve and enhance aquatic ecosystems and ensure long-term ecosystem health.